BaTiO3–Bi(Mg2/3Nb1/3)O3 Ceramics for High‐Temperature Capacitor Applications. Issue 6 (22nd March 2016) - Muhammad, Raz; Iqbal, Yaseen; Reaney, Ian M
Abstract : Solid solutions of (1− x )BaTiO3 – x Bi(Mg2/3 Nb1/3 )O3 (0 ≤ x ≤ 0.6) were prepared via a standard mixed‐oxide solid‐state sintering route and investigated for potential use in high‐temperature capacitor applications. Samples with 0.4 ≤ x ≤ 0.6 showed a temperature independent plateau in permittivity (εr ). Optimum properties were obtained for x = 0.5 which exhibited a broad and stable relative εr 940 ± 15% from 25°C to 550°C with a loss tangent <0.025 from 74°C to 455°C. The resistivity of samples increased with increasing Bi(Mg2/3 Nb1/3 )O3 concentration. The activation energies of the bulk were observed to increase from 1.18 to 2.25 eV with an increase in x from 0 to 0.6. These ceramics exhibited excellent temperature stable dielectric properties and are promising candidates for high‐temperature multilayer ceramic capacitors for automotive applications.